PEMBINAAN KETERAMPILAN BERKOMUNIKASI BAHASA INGGRIS PADA MASYARAKAT KARANG TARUNA PULAU JALOH BATAM - Sunargo Sunargo; Ambalegin Ambalegin; Poniman Poniman (ASOSIASI IDEBAHASA KEPRI, 2022)
Community potential can develop with the support of human resource skills. Batam as an archipelago has great potential in tourism and product development. In general, the development of infrastructure as a physical resource in the city of Batam has been sufficient to the islands around Batam, such as the island of Jaloh. The potential of the island as a national and foreign tourist spot needs the support of communication skills, especially English communication. most of the community activities are fishing and marine product management. In addition, the potential of the island as a tourist spot is an attraction for domestic and foreign tourists to visit and enjoy the beauty of the island of Jaloh. Based on community activities and the potential for island development, it is necessary to support English communication skills to make it easier to interact with visitors from abroad. This community service aims to improve English communication skills in supporting the potential of tourism islands and marine products. The achievement of the goals in this service is carried out using discussion and presentation methods regarding strategies and techniques of English communication skills. Coaching focuses on how to speak practically, practical speaking, pronunciation, daily vocabulary and listening. There needs to be coaching in communication in order to increase self-confidence. This activity is carried out for the youth community on Jaloh Island from December 2021 to June 2022. The results of community service, firstly, create cooperation in the field of community service between Putera Batam University and the people of Jaloh Island. Second, to increase insight and share knowledge of the service team to develop the potential of Jaloh Island community resources. Third, participants understand and have the knowledge and skills to communicate in English. Fourth, participants can achieve a competitive advantage in interacting through English communication. The implementation of activities can make a major contribution in developing the potential and building the advantages of the Jaloh Island community. The follow-up plan in the future is that community service activities are carried out by providing ongoing assistance and guidance. These activities can involve Batam city government officials to get encouragement and support.